The Role of Soil Type and Environmental Conditions in Increasing Soybean Production - Loso Judijanto; Dewa Oka Suparwata; Fatma Sarie; Safruddin Safruddin; Eko Sutrisno (West Science Agro, 2024)
Soybean stands as a critical crop globally, serving as a primary source of protein and oil. Optimizing soybean production is imperative to meet increasing demand amid evolving environmental and agronomic challenges. This qualitative analysis delves into the role of soil type and environmental conditions in enhancing soybean yield. Through a synthesis of existing literature and insights from interviews with key stakeholders, patterns and trends influencing soybean cultivation are identified. The findings underscore the complex interplay between soil properties, climatic factors, and agronomic practices in shaping soybean production dynamics. Tailored management strategies are essential for optimizing soil health, water management, and varietal selection to enhance soybean resilience and sustainability in the face of ongoing climate change and variability.